La multifunzionalità dell'agricoltura nelle zone montane marginali Una valutazione qualitativa, quantitativa e monetariadegli impatti ambientali, economici e sociali - Casini, Leonardo; Scozzafava, Gabriele (Proceedings e report, 2013)
This report contains the scientific results of the research project co-funded by Regione Toscana entitled "La multifunzionalità dell'agricoltura nelle zone montane marginali: una valutazione qualitativa, quantitativa e monetaria degli impatti ambientali, economici e sociali". The project involved various partners, whose skills enabled the activity to take an integrated, multi-disciplinary bent; the University of Florence Department of Farming and Forestry Economics, Engineering, Science and Technology - DEISTAF - took responsibility for the scientific side, while the local partners counted the municipality of San Godenzo, L'Unione dei Comuni della Montagna Fiorentina and the Consorzio Marrone del Mugello IGP. The general aim of the whole research project was to prepare guidelines for the endogenous and sustainable development of outlying areas, while extending knowledge of a fundamental aspect of farming, the primary activity, namely its multiple functions.